Learning Transformation: Applying SBM and the Principle of Equifinality in Facing Local Challenges - Sri Utaminingsih; Saiful Anwar; Ersam Mahendrawan (Educazione: Journal of Education and Learning, 2025)
This study focuses on the implementation of the principle of equifinality and School-Based Management (SBM) in early childhood education (ECE) in Serpong Subdistrict. The principle of equifinality provides flexibility for school principals to develop educational strategies tailored to local needs, while SBM emphasizes collaboration and decentralization in decision-making processes. This research aims to explore how these principles are applied in educational management and identify challenges faced during their implementation. The research employs a qualitative method with a case study approach, involving in-depth interviews, direct observation, and document analysis. Key respondents include school principals, teachers, and parents from several ECE institutions in the study area. The findings reveal that the principle of equifinality fosters innovation, such as project-based learning methods that respond to the specific needs of students. However, the success of this approach heavily depends on the availability of resources, which is a significant challenge for some schools. In the context of SBM, teachers are involved in lesson planning, but their participation in strategic decision-making remains limited. The involvement of parents and the community is also found to be low, reducing the effectiveness of the expected collaboration. The implications of this study highlight the need for policies that strengthen the managerial capacity of school principals and teachers, as well as enhance collaboration between schools, parents, and the community. This research contributes significantly to understanding the dynamics of locally-based educational management and its relevance to the needs of early childhood education, particularly in resource-limited areas